Cytoprotective Activity of Natural and Synthetic Antioxidants - Valentová, Kateřina (Antioxidants (Basel, Switzerland), 2020)
Numerous chronic diseases including cancer, cardiovascular, chronic respiratory or neurodegenerative diseases, diabetes mellitus, retinal damage, and others are associated with oxidative stress [...].